To Study the Properties of Concrete Mix on Partial Replacement of Coarse Aggregate with Burnt Bricks (International Journal of Innovative Research in Engineering & Management, 2023)
These days, materials such as over-burned  bricks blast are employed as an alternative to coarse  aggregates. This paper investigates the physical features of  concrete formed with burned bricks blast. Natural rock is  by far the most common coarse aggregate used in concrete,  however not all types of rock appropriate for concrete  production are available everywhere. Due to a paucity of  aggregate from natural sources in India's north-eastern  states, brick aggregate concrete is commonly utilised for  ordinary concrete. Due to advancements in concrete  technology and to meet the requirements for durability, As  a result of the need to utilise standard concrete, which only  uses stone aggregate, construction costs have increased as  materials are carried from other states. Making good  quality concrete with the finest sand (grading zone – IV as  per Indian code IS:383-1970) is difficult enough, but the  natural coarse aggregate is scarce locally. Burnt brick  aggregate has a high-water absorption rate (12 to 20% by  mass), which makes it difficult to utilise in practical work.  As a result, an attempt has been made to provide a viable  solution for real-world use. To test various strength  characteristics, an experimental investigation was done. In  our project, waste material was employed as a coarse  aggregate while simultaneously keeping the strength of the  concrete. The effects of a percentage replacement of stone  aggregates with burn brick aggregates on the compressive  strength of concrete are presented in this study. Concrete  cubes of M25 grade samples containing various  percentages of brick aggregate, such as 0%, 10%, 20%, and  30%, are made 7-, 14-, and 28-days tests were performed.
Keywords: Properties; Concrete; Replacement; Aggregate